Association between prenatal exposure to phthalate esters and blood pressure in children aged 3–7 years: A prospective cohort study - Zihao Wang; Yu Zhang; Wenwen Yang; Mengfei Xu; Beini Li; Ping Wu; Zhongqiang Cao; Wei Wu (Ecotoxicology and Environmental Safety)
Background: An increasing number of animal studies have indicated that exposure to phthalate esters (PAEs) may cause high blood pressure. However, population-based evidence is limited, particularly for pregnant women and young children. Objective: To examine the correlation between prenatal exposure to phthalate ester metabolites (mPAEs) and blood pressure in preschool children. Methods: In our cohort study, 497 pairs of mothers and children (aged 3–7 years) were enrolled at the Wuhan Maternal and Child Healthcare Hospital, Wuhan, China, between 2016 and 2017. Eight mPAEs were detected in the urine samples of pregnant women during the third trimester. Systolic (SBP) and diastolic blood pressure (DBP) were measured by physicians using an automated oscillometric sphygmomanometer and childhood hypertension was defined according to the American Academy of Pediatrics 2017 guidelines. Mixed-effects linear regression models were used to estimate the correlations between individual mPAEs and the SBP and DBP z-scores of preschoolers. Binary logistic regression models were used to examine the correlation between individual mPAEs and hypertension risk. A weighted quantile sum (WQS) regression was implemented to explore the correlation between mixed mPAEs and the SBP/DBP z-scores in children. Result: Monomethyl phthalate, monobutyl phthalate (MBP), monoethyl phthalate, mono(2-ethylhexyl) phthalate, mono(2-ethyl-5-hydroxyhexyl) phthalate and mono(2-ethyl-5-oxohexyl) phthalate were significantly positively correlated with increases in the SBP and DBP z-scores, whereas MBP was significantly correlated with hypertension risk, with an odds ratio of 1.695 (95 % confidence interval: 1.322, 2.173). Moreover, the WQS regression analyses revealed that MBP increased SBP (67.7 %) and DBP (80.8 %). Conclusions: The present study suggests that prenatal exposure to PAEs was positively correlated with increased blood pressure in pre-school children, and MBP is of particular concern because it contributed the most to the combined effect of PAE mixture on the risk of childhood hypertension.